2018
DOI: 10.5604/01.3001.0012.8660
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional accuracy and surface roughness of polymeric dental bridges produced by different 3D printing processes

Abstract: Purpose: To compare the dimensions accuracy and surface roughness of polymeric dental bridges produced by different 3D printers. Design/methodology/approach: Four-part dental bridges were manufactured by three printing systems working on the basis of digital light projection (DLP) stereolithography (SLA), laser-assisted SLA and fused deposition modeling (FDM). The materials used from SLA printers are liquid methacrylate photopolymer resins, while FDM printer use thin wire plastic polylactic acid. The accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 0 publications
2
45
0
Order By: Relevance
“…Compared with DLP technology, which uses a projector to cure one layer at a time, SLA technology uses a laser beam to cure the photopolymer material from point to line and surface [37]. Thus, more complete polymerization is achieved over the overall thickness of the layer [48]. As shown in Figure 4, D3P shows relatively dark colors for all prepared teeth compared to S3P.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with DLP technology, which uses a projector to cure one layer at a time, SLA technology uses a laser beam to cure the photopolymer material from point to line and surface [37]. Thus, more complete polymerization is achieved over the overall thickness of the layer [48]. As shown in Figure 4, D3P shows relatively dark colors for all prepared teeth compared to S3P.…”
Section: Discussionmentioning
confidence: 99%
“…Average surface roughness values (Ra/Sa) in different studies range widely: PMMA 0.02–6.2 µm [ 18 , 19 , 20 , 21 , 52 ], 3D printed PMMA (SLA) 0.39–2.97 µm [ 52 , 53 ], PEEK 0.032–2.52 µm [ 15 , 18 , 19 , 20 , 24 , 52 , 54 , 55 ], and PEKK 0.24–3.11 µm [ 56 , 57 ]. In some of these studies, cleaning protocol is either not stated or not used after polishing [ 24 , 52 , 53 ]. Most commonly, an ultrasonic bath filled either with water or alcohol (e.g., 70% ethanol or isopropanol) with consecutive water washing was used from 3 up to 20 min [ 15 , 18 , 20 , 21 , 54 , 55 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly, an ultrasonic bath filled either with water or alcohol (e.g., 70% ethanol or isopropanol) with consecutive water washing was used from 3 up to 20 min [ 15 , 18 , 20 , 21 , 54 , 55 , 57 ]. There is a high degree of heterogeneity in methodology: material specifications (inorganic filler content), surface finishing protocols, and significant variation of profilometry methods [ 15 , 18 , 20 , 21 , 24 , 52 , 53 , 54 , 55 , 56 , 57 ]. The results of the current study after both cleaning protocols are in the reported range for PMMA and PEEK but are lower for 3D printed PMMA and PEKK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). This was thought to be caused by the difference in fabrication methods between DLP 3D printing and self-curing [32,33]. Therefore, research on biocompatibility regarding micro leakage of temporary restorative materials are recommended for future research.…”
Section: Discussionmentioning
confidence: 99%